2014
DOI: 10.1155/2014/218637
|View full text |Cite
|
Sign up to set email alerts
|

Memory Functioning in Children with Epilepsy: Frontal Lobe Epilepsy, Childhood Absence Epilepsy, and Benign Epilepsy with Centrotemporal Spikes

Abstract: Specific cognitive deficits have been identified in children with epilepsy irrespective of results on intelligence tests. Memory deficits are traditionally attributed to temporal lobe epilepsy, whereas the impact of frontal lobe epilepsy on memory functions has remained controversial. The aim of this study was the examination of memory abilities in other childhood common epilepsy syndromes (frontal lobe epilepsy (FLE), childhood absence epilepsy (CAE), and benign epilepsy with centrotemporal spikes (BECTS)) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Interestingly, at the individual study level, significant age of onset effects, such that earlier age of onset is associated with poorer outcomes, were revealed for language function, long‐term storage and retrieval memory, processing speed, working memory, and fluid intelligence . These findings were not without contention, with other studies failing to find any significant effects related to age of onset .…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, at the individual study level, significant age of onset effects, such that earlier age of onset is associated with poorer outcomes, were revealed for language function, long‐term storage and retrieval memory, processing speed, working memory, and fluid intelligence . These findings were not without contention, with other studies failing to find any significant effects related to age of onset .…”
Section: Discussionmentioning
confidence: 84%
“…Worse performance in children with left versus right temporal lobe epilepsy on several measures, including immediate story recall, has been reported in by some authors (Jambaqué et al 2007) but not others (Jocic-Jakubi and Nebojsa 2006). When comparing different types of epilepsy, frontal lobe epilepsy was found to lead to worse performance on list learning than childhood absence epilepsy or benign epilepsy with centrotemporal spikes (Lopes et al 2014). In their extensive metaanalysis on memory in children with epilepsy, Menlove and Reilly (2015) concluded that the risks were largest with early age of seizure onset, longer duration of epilepsy, a greater number of anti-epileptic drugs and a higher number of seizures.…”
Section: Introductionmentioning
confidence: 78%
“…Children with epilepsy have an increased risk for memory problems (Menlove and Reilly 2015). When comparing children with epilepsy to typically developing children, studies have shown lowered memory scores on working memory, word lists and stories, irrespective of type of epilepsy (Gascoigne et al 2012;Jambaqué et al 1993;Lopes et al 2014;Northcott et al 2007;Rzezak et al 2017;van Iterson and de Jong 2018). Some conflicting evidence has been found for effects of lateralisation of seizures in focal epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, our study only included children with focal epilepsy in its epilepsy groups. Research suggests that individuals with simple partial epilepsy typically display deficits in encoding (Macleod et al, 1978; Lopes, Monteiro, Fonseca, Robalo, & Simões, 2014), whereas children with complex partial seizures often experience a wide range of memory problems (Von Isser, 1977; Williams, 2003). Thus, both populations may experience problems with encoding, and those with complex partial seizures may experience additional memory problems.…”
mentioning
confidence: 99%